2001
DOI: 10.1034/j.1601-0825.2001.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term exposure to alcohol increases the permeability of human oral mucosa

Abstract: These results suggest that short-term exposure to ethanol may act as a permeability enhancer, possibly by causing molecular rearrangement of the permeability barrier, not as a result of lipid extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 34 publications
(39 reference statements)
1
50
0
4
Order By: Relevance
“…It has been suggested that alcohol may modify the cellular metabolism of carcinogens, 32 that its metabolite, acetaldehyde, is responsible for enhanced risk, 33,34 that excessive use may lead to nutritional deficiencies enhancing risk, 35 and that alcohol itself may simply solubilize carcinogens and enhance their penetration into cells. 36 Our data suggest that alcohol may act as a selective agent, promoting growth of cells with SFRP1 promoter methylation, and that the effect is independent of the effect of tobacco, with both light and heavy drinking cases showing similar elevated relative risks of SFRP1 promoter methylation (ORs 3.7 and 3.5, respectively) compared to nondrinking cases. This activity may be mediated through an effect on the carcinogen penetration or metabolism or through another growth promoting mechanism such as injury response.…”
Section: Discussionmentioning
confidence: 73%
“…It has been suggested that alcohol may modify the cellular metabolism of carcinogens, 32 that its metabolite, acetaldehyde, is responsible for enhanced risk, 33,34 that excessive use may lead to nutritional deficiencies enhancing risk, 35 and that alcohol itself may simply solubilize carcinogens and enhance their penetration into cells. 36 Our data suggest that alcohol may act as a selective agent, promoting growth of cells with SFRP1 promoter methylation, and that the effect is independent of the effect of tobacco, with both light and heavy drinking cases showing similar elevated relative risks of SFRP1 promoter methylation (ORs 3.7 and 3.5, respectively) compared to nondrinking cases. This activity may be mediated through an effect on the carcinogen penetration or metabolism or through another growth promoting mechanism such as injury response.…”
Section: Discussionmentioning
confidence: 73%
“…Prolonged exposure may also sensitize peripheral nerve-endings, leading to diminished response, since ethanol destroys nervous tissue by extracting cholesterol and other lipids and by protein precipitation (21). There are several other mechanisms by which ethanol might affect oral mucosa, such as oxidizing activity that leads to changes by directly injuring DNA (22) and increased carcinogen penetration across the oral mucosa, perhaps due to increased mucosal permeability (23), which increases with increasing alcohol concentration (24). Kuyama et al (25) studied the effects of alcohol on oral mucosal cells in 125 subjects and found increased keratinization of oral mucosal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism by which alcoholic beverages may increase the risk of cancer is the potential for such beverages to contain various carcinogenic congers and contaminants. In addition, alcohol may (a) interfere with nutritional intake or bioavailability, (b) enhance the penetration of carcinogens within the oral mucosa, (c) reduce immune function, (d) potentiate the genotoxicity of or activate carcinogenic agents, (e) interfere with DNA repair and (f) inhibit the detoxification of carcinogens [36][37][38][39].…”
Section: Alcohol Consumptionmentioning
confidence: 99%